Errata - de Editoração, Núcleo (Revista de Nutrição, 2023)
No artigo “Dietary intake of patients with Nonalcoholic Fatty Liver Disease: Comparison between the presence and absence of Nonalcoholic Steatohepatitis and Metabolic Syndrome”, com n° de DOI: http://dx.doi.org/10.1590/1678-98652016000400005, publicado no periódico Revista de Nutrição, 29(4):495-505, na página 495: Onde se lia: Dietary intake of patients with Nonalcoholic Fatty Liver Disease: Comparison between the presence and absence of Nonalcoholic Steatosis and Metabolic Syndrome Leia-se: Dietary intake of patients with Nonalcoholic Fatty Liver Disease: Comparison between the presence and absence of Nonalcoholic Steatohepatitis and Metabolic Syndrome